Economic effectiveness of operation and utilization of large container carriers - Široký Jaromír; Chalupová Vohánková Hana (My University, 2016)
This paper deals with operational effectiveness of large container carriers transporting standardized transportation units. The calculation is related to costs per one TEU transported. What is a very important factor in maritime transport is the vessel's speed. Speed has a considerable influence on total costs, and that's why this factor is also taken into consideration in the calculation. Besides speed, there is another important factor, i.e. the utilization of the capacity of container ships, and that's why new container ship types (Suezmax and Triple-E) were considered in the calculation. In the conclusion, other factors are stated that are of importance for establishing the utilization and economic effectiveness of the given types of container ships.
Ekonomická efektivita provozu a vytíženost velkých kontejnerových nosičů
Keywords: Container; effectiveness; container ship; maritime transport; kontejner; efektivita; kontejnerová loď; námořní doprava